Guarantying Ministerial Integrity of The New Indonesian Government - Sidqul Anwar, Dadan (Iapa Proceedings Conference, 2024)
The new Indonesian government provides new hope for a better Indonesia and even achieving a Golden Indonesia in 2045. To realize this hope it is necessary to ensure that the main players in the cabinet, the ministers are truly in line with the value of integrity because integrity is one of the main foundations in the new government. In line with this argument, Dwight D. Eisenhower also positioned integrity as the supreme quality of leadership. However, until recently, and who knows how long, Indonesia will still be plagued by integrity violations, especially ministerial corruption. For example, recently the Minister of Agriculture, SYL, has become part of the latest corruption phenomenon. Not only recently, even ministerial corruption has occurred in almost every government regime. This tendency might prove that ministerial corruption might also threaten the new government. This real threat certainly needs to be resolved. To do so, creating an integrity system for ministerial positions is urgent. Therefore, integrity-based recruitment of Ministers and a ministerial code of ethics may be important ways to guarantee the integrity of ministerial positions in the new government.